Gambaran Pengetahuan Bahaya Minuman Keras pada Remaja - Endang Sawitri; Chory Elsera; Esri Rusminingsih; Alvina Hafidiati (TRIAGE Jurnal Ilmu Keperawatan, 2024)
Alcoholic Beverages is a drink that contains ethanol (alcohol) in high concentrations. Alcohol in liquor is a psychoactive substance that can affect the central nervous system, causing changes in consciousness, mood and behavior. Alcohol abuse causes 1.8 million deaths worldwide. According to the World Health Organization (WHO) in 2019, alcohol consumption was responsible for more than 55,000 deaths in people aged 15-29 years in Europe. Alcohol and health are recognized globally as many as 320,00 people aged 15-29 years die every year due to alcohol. Research objective: To determine the knowledge of the dangers of alcoholic beverages among adolescents. Method: The research design uses quantitative descriptive research methods. The research population was teenagers in Tegal Hamlet, Tirto Village, Salam District, Magelang Regency, Central Java Province. totaling 54 respondents. The sampling technique uses total sampling, namely the entire number of respondents. Data analysis was carried out using frequency distribution. Results: The characteristics of the teenagers who were respondents were an average of 17.87 years old. The majority of respondents were female, namely 33 (61.1%). The majority of teenagers with junior high school education were 22 people (40.7%). The results of this research obtained a good level of knowledge with a total of 42 respondents (77.8%). Conclusion: shows that of the 54 teenagers respondents, the average age was 16-17 (56.67%), the majority gender was female (61.1%). Most education is in junior high school (40.7%), teenagers' knowledge about the dangers of drinking is in the good category (77.8%).